Oxygen Isotope Dendrochronology of the Newport Medieval Ship - Neil Loader (International Journal of Nautical Archaeology, 2024)
Since the discovery of the Newport Medieval Ship in 2002, many studies have tried to establish a chronology for its construction and subsequent abandonment. Whilst conventional ring-width dendrochronology has been able to identify the provenance and provide a terminus post quem for the ship, until now a felling date for timbers associated with the original construction of the vessel has proved elusive. This study reports results from the application of stable isotope dendrochronology to date timbers from the ship. Using a combination of dendrochronologically-dated timbers and stable oxygen isotopic data from dated and undated samples, we can provide an independent verification of the ring-width dendrochronology and to return the first felling dates for an assemblage of the ship’s framing timbers. Our results indicate that the ship was likely constructed shortly after the winter of AD 1457/8 with an operational lifetime of less than a decade. The study highlights the potential for the use of stable isotope dendrochronology for the precise, absolute dating of archaeological ship remains where ring-width dendrochronology alone has not proved effective.